Discrimination by default : how racism becomes routine - Wang, Lu-in (Critical America., 2006)
Much as we "select" computer settings by default-reflexively, without thinking, and sometimes without realizing there are other options-we often discriminate by default as well. And just as default computer settings tend to become locked in or entrenched as the standard, discrimination by default creates a situation in which disparate outcomes are expected, accepted, and taken for granted. The killing of Amadou Diallo, racial disparities in medical care, the dominance of Whites and men in certain professions, and even the uneven media attention paid to crimes depending on their victims' race a